2018
DOI: 10.1016/j.jdermsci.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils contribute to vasculitis by increased release of neutrophil extracellular traps in Behçet's disease

Abstract: Our results provide evidence on the implication of NETosis in the pathophysiology of BD especially in inducing vasculitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 23 publications
1
86
1
2
Order By: Relevance
“…Interestingly, these cytokines are increased in BD and IL17, TNFα and IL-1β play an important role in Behçet-associated inflammation 4. In a recent study, NETs from patients BD have been shown to contribute to the endothelial dysfunction by decreasing cell proliferation and increasing cell apoptosis suggesting a role of NETs beyond thrombosis 33. Interestingly, treatments widely used in BD such as colchicine, anti-TNFα or anti IL-6 were recently found to inhibit in vitro NETs extrusion and further abridged the endothelial dysfunction and the activation of immune cells, thus influencing the global activity of the vascular system.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these cytokines are increased in BD and IL17, TNFα and IL-1β play an important role in Behçet-associated inflammation 4. In a recent study, NETs from patients BD have been shown to contribute to the endothelial dysfunction by decreasing cell proliferation and increasing cell apoptosis suggesting a role of NETs beyond thrombosis 33. Interestingly, treatments widely used in BD such as colchicine, anti-TNFα or anti IL-6 were recently found to inhibit in vitro NETs extrusion and further abridged the endothelial dysfunction and the activation of immune cells, thus influencing the global activity of the vascular system.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil inflammatory responses may be considered a double-edged sword; although they protect against infection, they also cause severe tissue damage. Activated neutrophils are involved in many acute and chronic inflammatory diseases as well as autoimmune disorders, such as respiratory diseases (ARDS, COPD, and asthma), cardiovascular diseases (atherosclerosis and thrombosis) ( Németh et al, 2020 ), gastrointestinal diseases (inflammatory bowel disease and autoimmune hepatitis) ( Honda and Kubes, 2018 ), neurological diseases (multiple sclerosis and Alzheimer’s disease) ( Dong et al, 2018 ; Woodberry et al, 2018 ), skin diseases (psoriasis and Behçet’s disease) ( Safi et al, 2018 ; Chiang et al, 2019 ), and metabolic diseases (diabetes mellitus and obesity) ( Talukdar et al, 2012 ; Brotfain et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“… 23 24 Thus, it interferes with both neutrophil chemotaxis and NETosis. 25 Safi et al 15 have recently demonstrated that NETs formation in BD neutrophils was inhibited by colchicine. In addition, in vitro studies have shown that colchicine decreased expression of surface markers of platelet activity and inhibited leukocyte-platelet aggregation.…”
Section: Scientific Hypothesis and Its Limitationsmentioning
confidence: 99%
“… 14 The structure of NETs differs between different diseases but there are some markers that could be used to follow NETosis in BD such as peptidylarginine deiminase 4 (PAD4). 15 PAD4 promotes a key event in NETosis which is citrullination of arginine residues on chromatin. 16 Neutrophils from BD patients were shown to be more prone to NETosis even in the absence of stimuli in vitro, and the amount of NETs was higher in BD patients with vascular involvement compared to the ones without vascular involvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation